2000
DOI: 10.1007/s007870070003
|View full text |Cite
|
Sign up to set email alerts
|

Number processing and mental calculation in school children aged 7 to 10 years: a transcultural comparison

Abstract: Neuropsychological studies of dyscalculic patients show that arithmetical development is not a unidimensional process. In transcultural investigations, cultural, educational and linguistic factors might affect differently the various components of mathematical development. Four hundred and sixty schoolchildren aged 7 to 10 years from Brasilia, Brazil (n = 141), Paris, France (n = 160) and Zurich, Switzerland (n = 159) were asked to perform eleven number processing and calculation tasks. Chronological age, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 20 publications
1
36
0
6
Order By: Relevance
“…In previous studies it was suggested that a low socioeconomic level and educational environment could determine such differences (Dellatolas et al, 2000;Koumoula et al, 2004). In the present study, socioeconomic status was objectively assessed, rather than inferred by the environment factor, and the statistical analysis indicated that rural children in fact had low socioeconomic scores than urban children.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In previous studies it was suggested that a low socioeconomic level and educational environment could determine such differences (Dellatolas et al, 2000;Koumoula et al, 2004). In the present study, socioeconomic status was objectively assessed, rather than inferred by the environment factor, and the statistical analysis indicated that rural children in fact had low socioeconomic scores than urban children.…”
Section: Discussionmentioning
confidence: 52%
“…In the BDS, the subject repeats the digits in reverse order. Additionally, as presented by Dellatolas et al (2000), the Score A is SANTOS, SILVA, RIBEIRO, DIAS, FRIGÉRIO, DELLATOLAS, AND VON ASTER 518 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional analysis confirmed that sub-tests NUCALC could be organized into three clusters, fitting well with the three modules of Dehaene's triple code model (Santos et al, 2013;von Aster, 2000). There have been behavioral studies that used NUCALC to examine the age or grade effect on children across countries (Dellatolas, von Aster, Willadino-Braga, Meier, & Deloche, 2000;Koumoula et al, 2004;Santos et al, 2013). These studies revealed an agerelated improvement in Score A, which consisted of six subtests that were associated with schooling achievement (dictation and reading of numbers, mental calculation addition part, problem solving, and oral and written comparison).…”
Section: The Development Of the Three Modulesmentioning
confidence: 55%
“…Com a inserção no Ensino Fundamental, as crianças aprendem a representar os números por meio do processamento simbó-lico (p.ex., palavras, numerais, ideogramas), o que permite a manipulação e comparação de quantidades precisas (Mundy & Gilmore, 2009). Uma vez que as habilidades quantitativas adquirem características culturais (Geary, 2000;von Aster & Shalev, 2007), fatores linguísticos, culturais e pedagógicos têm diferentes efeitos nos diversos componentes das habilidades matemáticas e podem, em alguns casos, afetar a aprendizagem escolar (Dellatolas, von Aster, Braga, Meier, & Deloche, 2000).…”
unclassified